Penilaian BK di Sekolah dan Implikasi Pengelolaanya - Indra Saputra; Firman; Neviyarni (Education & Learning, 2022)
Assessment is an important step in the management of Guidance and Counseling (BK). Without an assessment it is impossible for us to know and identify the success of the implementation of the planned guidance program. Assessment of the guidance program is an attempt to assess the extent to which the implementation of the program has achieved the stated goals. In other words, the success of the program in achieving goals is a condition to be seen through assessment activities. Assessment of guidance and counseling service activities in schools is all efforts, actions or processes to determine the degree of quality progress of activities related to the implementation of guidance and counseling programs in schools by refers to certain criteria or benchmarks in accordance with the program being implemented